Kyrgyz Republic Economic Update, No.9, Fall 2019 : Strong Growth Led by the Gold Sector – With a Special Focus on Public Investment Management - World Bank Group (World Bank, Washington, DC, 2020)
Gold production increased substantially in 2019, providing a strong boost to economic growth. Output from the country's largest gold mine, Kumtor, rose by 33 percent year on year in January-October, a reversal from the 8 percent contraction in the same period of 2018. As a result, real GDP grew by 5.7 percent in January-October, up from 3.5 percent in 2018 as a whole. Gold exports, which increased by almost 55 percent year on year, contributed to strong export earnings and a narrower current account deficit. Monetary policy easing and continued remittance inflows also supported GDP growth. Real GDP is projected to grow by 4.2 percent in full-year 2019, as gold production growth is slowing in the last three months of the year. Economic activity is likely to keep the same pace in the medium term as gold production volume will stay at the current level. The current account deficit is expected to remain wide despite rising remittances. The fiscal deficit widened slightly in January-September 2019 owing to lower tax revenues as a percentage of GDP (mainly due to reduced receipts from import taxes). As investment spending accelerates in the second half of the year—and a 30-percent wage increase for teachers took effect in October— the budget deficit is likely to widen to 3.2 percent of GDP in 2019 from 1.6 percent of GDP in 2018. The government plans to reduce the fiscal deficit to 3 percent of GDP in 2020 in line with the fiscal rule; the latter is currently pending parliamentary approval. Improving expenditure management has been a key challenge in the Kyrgyz Republic, especially in the context of the need to create the much-needed fiscal space for investment in infrastructure and human capital. The special focus section explores the main issues related to public investment management and discusses how to enhance the selection, assessment, and evaluation processes of public investment projects.